К ВОПРОСУ О ФЕТАЛЬНОМ ПРОГРАММИРОВАНИИ ОЖИРЕНИЯ У ДЕТЕЙ - Петренко, Юрий Валентинович; Прокопьева, Наталья Эдуардовна; Иванов, Дмитрий Олегович; Похлебкина, Алевтина Алексеевна; Гурина, Ольга Петровна; Блинов, Александр Евгеньевич; Варламова, Ольга Николаевна; Леваднева, Марина Ивановна; Тарханова, Елена Борисовна; Новикова, Валерия Павловна (FORCIPE, 2022)